Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

The effect of environmental pollution on gene expression of seabirds: A review - Randel Kreitsberg; Lisanne Nääb; Richard Meitern; Jeffrey Carbillet; Jérôme Fort; Mathieu Giraudeau; Tuul Sepp (Marine Environmental Research, 2023)

Carryover effects of winter mercury contamination on summer concentrations and reproductive performance in little auks - Alice Carravieri; Sophie Lorioux; Frédéric Angelier; Olivier Chastel; Céline Albert; Vegard Sandøy Bråthen; Émile Brisson-Curadeau; Manon Clairbaux; Karine Delord; Mathieu Giraudeau; Samuel Perret; Timothée Poupart; et al. (Environmental Pollution, 2023)

Telomeres, the loop tying cancer to organismal life‐histories - Beata Ujvari; Nynke Raven; Thomas Madsen; Marcel Klaassen; Antoine M. Dujon; Aaron G. Schultz; Leonard Nunney; Jean‐François Lemaître; Mathieu Giraudeau; Frédéric Thomas (Molecular Ecology, 2022)
Recent developments in telomere and cancer evolutionary ecology demonstrate a very complex relationship between the need of tissue repair and controlling the emergence of abnormally proliferating cells. The trade‐off is balanced by natural and sexual selection and mediated via both intrinsic and environmental factors. Here, we explore the effects of telomere‐cancer dynamics on life history traits and strategies as well as on the cumulative effects of genetic and environmental factors. We show that telomere‐cancer dynamics constitute an incredibly complex and multifaceted process. From research to date, it appears that the relationship between telomere length and cancer risk is likely nonlinear with good evidence that both (too) long and (too) short telomeres can be associated with increased cancer risk. The ability and propensity of organisms to respond to the interplay of telomere dynamics and oncogenic processes, depends on the combination of its tissue environments, life history strategies, environmental challenges (i.e., extreme climatic conditions), pressure by predators and pollution, as well as its evolutionary history. Consequently, precise interpretation of telomere‐cancer dynamics requires integrative and multidisciplinary approaches. Finally, incorporating information on telomere dynamics and the expression of tumour suppressor genes and oncogenes could potentially provide the synergistic overview that could lay the foundations to study telomere‐cancer dynamics at ecosystem levels.

Parental age does not influence offspring telomeres during early life in common gulls ( Larus canus ) - Tuul Sepp; Richard Meitern; Britt Heidinger; Kristina Noreikiene; Kalev Rattiste; Peeter Hõrak; Lauri Saks; Jeffrey Kittilson; Janek Urvik; Mathieu Giraudeau (Molecular Ecology, 2022)
Parental age can affect offspring telomere length through heritable and epigenetic‐like effects, but at what stage during development these effects are established is not well known. To address this, we conducted a cross‐fostering experiment in common gulls ( Larus canus ) that enabled us distinguish between pre‐ and post‐natal parental age effects on offspring telomere length. Whole clutches were exchanged after clutch completion within and between parental age classes (young and old) and blood samples were collected from chicks at hatching and during the fastest growth phase (11 days later) to measure telomeres. Neither the ages of the natal nor the foster parents predicted the telomere length or the change in telomere lengths of their chicks. Telomere length (TL) was repeatable within chicks, but increased across development (repeatability = 0.55, intraclass correlation coefficient within sampling events 0.934). Telomere length and the change in telomere length were not predicted by post‐natal growth rate. Taken together, these findings suggest that in common gulls, telomere length during early life is not influenced by parental age or growth rate, which may indicate that protective mechanisms buffer telomeres from external conditions during development in this relatively long‐lived species.

Pesticide impacts on avian species with special reference to farmland birds: a review - Jérôme Moreau; Juliette Rabdeau; Isabelle Badenhausser; Mathieu Giraudeau; Tuul Sepp; Malaury Crépin; Agathe Gaffard; Vincent Bretagnolle; Karine Monceau (Environmental Monitoring and Assessment, 2022)

Darwin, the devil, and the management of transmissible cancers - Rodrigo Hamede; Thomas Madsen; Hamish McCallum; Andrew Storfer; Paul A. Hohenlohe; Hannah Siddle; Jim Kaufman; Mathieu Giraudeau; Menna Jones; Frédéric Thomas; Beata Ujvari (Conservation Biology, 2021)

Light at night reduces digestive efficiency of developing birds: an experiment with king quail - Tuul Sepp; Emily Webb; Richard K. Simpson; Mathieu Giraudeau; Kevin J. McGraw; Pierce Hutton (The Science of Nature, 2021)

A review of urban impacts on avian life‐history evolution: Does city living lead to slower pace of life? - Tuul Sepp; Kevin J. McGraw; Ants Kaasik; Mathieu Giraudeau (Global Change Biology, 2018)
The concept of a pace‐of‐life syndrome describes inter‐ and intraspecific variation in several life‐history traits along a slow‐to‐fast pace‐of‐life continuum, with long lifespans, low reproductive and metabolic rates, and elevated somatic defences at the slow end of the continuum and the opposite traits at the fast end. Pace‐of‐life can vary in relation to local environmental conditions (e.g. latitude, altitude), and here we propose that this variation may also occur along an anthropogenically modified environmental gradient. Based on a body of literature supporting the idea that city birds have longer lifespans, we predict that urban birds have a slower pace‐of‐life compared to rural birds and thus invest more in self maintenance and less in annual reproduction. Our statistical meta‐analysis of two key traits related to pace‐of‐life, survival and breeding investment (clutch size), indicated that urban birds generally have higher survival, but smaller clutch sizes. The latter finding (smaller clutches in urban habitats) seemed to be mainly a characteristic of smaller passerines. We also reviewed urbanization studies on other traits that can be associated with pace‐of‐life and are related to either reproductive investment or self‐maintenance. Though sample sizes were generally too small to conduct formal meta‐analyses, published literature suggests that urban birds tend to produce lower‐quality sexual signals and invest more in offspring care. The latter finding is in agreement with the adult survival hypothesis, proposing that higher adult survival prospects favour investment in fewer offspring per year. According to our hypothesis, differences in age structure should arise between urban and rural populations, providing a novel alternative explanation for physiological differences and earlier breeding. We encourage more research investigating how telomere dynamics, immune defences, antioxidants and oxidative damage in different tissues vary along the urbanization gradient, and suggest that applying pace‐of‐life framework to studies of variation in physiological traits along the urbanization gradient might be the next direction to improve our understanding of urbanization as an evolutionary process.

Carotenoid coloration is related to fat digestion efficiency in a wild bird - Christina Madonia; Pierce Hutton; Mathieu Giraudeau; Tuul Sepp (The Science of Nature, 2017)

Colour polymorphism is associated with lower extinction risk in birds - Simon Ducatez; Mathieu Giraudeau; Christophe Thébaud; Lisa Jacquin (Global Change Biology, 2017)
Colour polymorphisms have played a major role in enhancing current understanding of how selection and demography can impact phenotypes. Because different morphs often display alternative strategies and exploit alternative ecological niches, colour polymorphism can be expected to promote adaptability to environmental changes. However, whether and how it could influence populations' and species' response to global changes remains debated. To address this question, we built an up‐to‐date and complete database on avian colour polymorphism based on the examination of available data from all 10,394 extant bird species. We distinguished between true polymorphism (where different genetically determined morphs co‐occur in sympatry within the same population) and geographic variation (parapatric or allopatric colour variation), because these two patterns of variation are expected to have different consequences on populations' persistence. Using the IUCN red list, we then showed that polymorphic bird species are at lesser risk of extinction than nonpolymorphic ones, after controlling for a range of factors such as geographic range size, habitat breadth, life history, and phylogeny. This appears consistent with the idea that high genetic diversity and/or the existence of alternative strategies in polymorphic species promotes the ability to adaptively respond to changing environmental conditions. In contrast, polymorphic species were not less vulnerable than nonpolymorphic ones to specific drivers of extinction such as habitat alteration, direct exploitation, climate change, and invasive species. Thus, our results suggest that colour polymorphism acts as a buffer against environmental changes, although further studies are now needed to understand the underlying mechanisms. Developing accurate quantitative indices of sensitivity to specific threats is likely a key step towards a better understanding of species response to environmental changes.

Parasites, mate attractiveness and female feather corticosterone levels in a socially monogamous bird - François Mougeot; Ádám Z. Lendvai; Jesús Martínez-Padilla; Lorenzo Pérez-Rodríguez; Mathieu Giraudeau; Fabián Casas; Ignacio T. Moore; Steve Redpath (Behavioral Ecology and Sociobiology, 2016)

Effects of carotenoid supplementation and oxidative challenges on physiological parameters and carotenoid-based coloration in an urbanization context - Mathieu Giraudeau; Afton Chavez; Matthew B. Toomey; Kevin J. McGraw (Behavioral Ecology and Sociobiology, 2015)

Nutritional status does not explain the increase of carotenoid-based coloration associated with age in Great Tits Parus major - Mathieu Giraudeau; Margarida Barcelo; Juan Carlos Senar (Journal of Ornithology, 2014)

Preen gland removal increases plumage bacterial load but not that of feather-degrading bacteria - Gábor Árpád Czirják; Péter László Pap; Csongor István Vágási; Mathieu Giraudeau; Cosmin Mureşan; Pascal Mirleau; Philipp Heeb (The Science of Nature, 2013)

Can House Finches (Carpodacus mexicanus) use non-visual cues to discriminate the carotenoid content of foods? - Mathieu Giraudeau; Matthew B. Toomey; Kevin J. McGraw (Journal of Ornithology, 2012)

Effects of access to preen gland secretions on mallard plumage - Mathieu Giraudeau; Camille Duval; Noel Guillon; Vincent Bretagnolle; Claude Gutierrez; Philipp Heeb (The Science of Nature, 2010)